CATEGORY IN TRADITIONAL AND COGNITIVE GRAMMAR INTERPRETATION OF THE CONCEPT (Conference Zone, 2022)
This article analyzes the expansion of the scope of this discipline, which has so far analyzed the language system and text structure, which is the product of speech activity, from a philological point of view, with concepts and categories related to cognitive, cognitive, analytical activities